Africans in Britain, 1500-1640 - Kaufmann, M (2011)
This study of Africans in Britain 1500-1640 employs evidence from a wide range of primary sources including parish registers, tax returns, household accounts, wills and court records to challenge the dominant account, which has been overly influenced by the language of Shakespeare’s Othello and other contemporary literature. I explain the international context of growing trade and increased diplomatic relations with Africa and a concomitant increased level of contact with Africans in the Atlantic world. I then explore the ways in which Africans might come to Britain. Some travelled via Europe in the entourages of royals, gentlemen or foreign merchants; some came from Africa to train as trade factors and interpreters for English merchants; large numbers arrived as a result of privateering activity in which they were captured from Spanish and Portuguese ships. Once in Britain, they were to be found in every kind of household from those of kings to seamstresses. Some were entirely independent, some poor, though few resorted to crime. They performed a wide range of skilled roles and were remunerated in the same mix of wage, reward and gifts in kind as others. They were accepted into society, into which they were baptized, married and buried. They inter-married with the local population and had children. Africans accused of fornication and men who fathered illegitimate children with African women were punished in the same way as others. The legacy of villeinage coupled with the strong rhetoric of freedom in legal and popular discourse ensured that Africans in Britain were not viewed as slaves in the eyes of the law. Neither were they treated as such. They were paid wages, married, and allowed to testify in court. Those scholars who have sought to place the origins of racial slavery in Elizabethan and early Stuart England must now look elsewhere.